Plasma levels of TNF-α, IFN-γ, IL-4 and IL-10 during a course of experimental contagious bovine pleuropneumonia - Sacchini, F.; Luciani, M.; Salini, R.; Scacchia, M.; Pini, A.; Lelli, R.; Naessens, Jan; Poole, Elizabeth J.; Jores, Joerg (Springer, 2012)
Contagious Bovine Pleuropneumonia (CBPP), caused by Mycoplasma mycoides subsp. mycoides, is widespread in sub-Saharan Africa. The current live vaccine T1/44 has limited efficacy and occasionally leads to severe side effects in the animals. A better understanding of the immune responses triggered by Mycoplasma mycoides subsp. mycoides and their role in disease progression will help to facilitate the design of a rational vaccine. Currently, knowledge of cytokines involved in immunity and immunopathology in CBPP is rather limited. The aim of this study was to characterize the in vivo plasma concentrations of the cytokines TNF-alpha, IFN-gamma, IL-4, IL-10 and the overall role of CD4+ T cells in the development of cytokine levels during a primary infection. Plasma cytokine concentrations in two groups of cattle (CD4+ T cell-depleted and non-depleted cattle) experimentally infected with Mycoplasma mycoides subsp. mycoides were measured and their relationship to the clinical outcomes was investigated.